2004
DOI: 10.1159/000081760
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Formoterol or Montelukast to Low-Dose Budesonide: An Efficacy Comparison in Short- and Long-Term Asthma Control

Abstract: Background: Asthma is a chronic inflammatory disease of the airways. Inhaled corticosteroids are very important in anti-inflammatory treatment, but to a great extent they cannot control asthma alone. In addition to corticosteroids, long-acting β2 agonists and leukotriene antagonists are used for asthma control. Objective: In this study, the effect of the addition of formoterol and montelukast on asthma control in patients with moderately persistent asthma who were symptomatic while using a low dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…13 As per our study, the FB group showed significantly greater improvement in PEF and FEV1. This is in accordance with studies done by Ringdal et al, Ceylan et al 14,15 The fact that mean values of PEF of FB group were significantly greater than that of MB group throughout the study period showed that FB treatment was better than MB treatment in improving lung function right from the first week after the start of the respective treatments. This significant superiority of LABA over LTRA in improving PEF at a much earlier point in the course of treatment was also shown in the 2 week study by Wilson and his colleagues.…”
Section: Discussionsupporting
confidence: 92%
“…13 As per our study, the FB group showed significantly greater improvement in PEF and FEV1. This is in accordance with studies done by Ringdal et al, Ceylan et al 14,15 The fact that mean values of PEF of FB group were significantly greater than that of MB group throughout the study period showed that FB treatment was better than MB treatment in improving lung function right from the first week after the start of the respective treatments. This significant superiority of LABA over LTRA in improving PEF at a much earlier point in the course of treatment was also shown in the 2 week study by Wilson and his colleagues.…”
Section: Discussionsupporting
confidence: 92%
“…However, for its clinical significance in the treatment of moderate to severe persistent asthma [30], dexamethasone was used to investigate inhibition of eotaxin protein production in human ASMC and HMC-1 cocultures. Human ASMC pretreated for 24 h at 1 µ M dexamethasone was able to significantly inhibit eotaxin protein production as detected in 24-hour supernatants (fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study done by Ceylan et al [33] in patients with moderately persistent asthma, similar in study duration and patient selection, compared formoterol (9 µg) and montelukast (10 mg) added to budesonide 400 µg daily during a follow-up of up to 8 weeks. It showed greater improvement in the group treated with formoterol plus budesonide compared to the group receiving montelukast plus budesonide.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Ceylan et al [33] has demonstrated that formoterol causes a considerable improvement in lung function and showed better asthma control than montelukast treatment in patients with moderately persistent asthma.…”
Section: Discussionmentioning
confidence: 99%